Managing Defence Acquisition Cost Growth. Issue 1 (2nd January 2017) - Bangert, David; Davies, Neil; Watson, Ryan
Abstract: This article reviews the previous literature on the cost escalation of defence equipment and provides estimates for Royal Navy platforms over the past 55 years. David Bangert, Neil Davies and Ryan Watson examine the experience of other European states and previous unsuccessful attempts to address the problem in the UK and other European countries. They conclude that while the problem cannot be ignored, solutions will be painful.